Interactive Powerpoint Nervous System Material: A Learning Media Development Research - Sari, Danning Wulan; Filayani, Muhammad Iqbal (Universitas Islam Negeri Walisongo Semarang, 2023)
Nervous system material tends to be difficult to understand and many theories need to be conveyed concisely and interestingly. This research aims to develop learning media in the form of interactive powerpoints on nervous system material that can improve learning outcomes. The research and development model uses the ADDIE model. Data collection methods use observation, interviews and questionnaires. Validity trials were carried out by material expert lecturers and media experts. Meanwhile, the practicality test was carried out by the class XI biology subject teacher and 20 students. The data analysis technique used is qualitative and quantitative descriptive analysis. The research results show that the average validity of each interactive PowerPoint is 75% in the valid category. The average practicality value for interactive PowerPoint is respectively 90% and 86.85% in the very practical category as a learning medium. Then the t-test results obtained sig. (2-tailed) of 0.001 < 0.05, indicating that interactive PowerPoint learning media is effective in improving student learning outcomes.